Polymorphism of Prodynorphin promoter is associated with schizophrenia in Chinese population - ZHANG Chang-shun; TAN Zheng; YU Lan; WU Sheng-nan; HE Ying; GU Niu-fan; FENG Guo-yin; HE Lin (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the correlation between single nucleotide polymorphisms (SNPs) of functional candidate gene Prodynorphin (PDYN) and schizophrenia. METHODS: SNPs in the promoter and exon regions of PDYN were screened and genotyped for association study in a cohort of Chinese Han schizophrenia cases and controls. RESULTS: Two SNPs PDYN-1576C>T and PDYN-946C>G were identified in the promoter region but PDYN-946C>G showed significant differences of allele distribution (x2=6.15, P=0.013) and genotype distribution (x2=6.87, P=0.032) between schizophrenic and control subjects. CONCLUSION: PDYN-946C>G polymorphism demonstrated an association with population susceptibility to schizophrenia.